2015
DOI: 10.1080/08998280.2015.11929174
|View full text |Cite
|
Sign up to set email alerts
|

Postextubation Dysphagia

Abstract: Postextubation dysphagia (PED) is a common problem in critically ill patients with recent intubation. Although several risk factors have been identified, most of them are nonmodifiable preexisting or concurrent conditions. Early extubation, small endotracheal tube size, and small bore of nasogastric tube potentially decrease the risk of PED. The majority of patients receive treatment based on only bedside swallow evaluations, which has an uncertain diagnostic accuracy as opposed to gold standard instrumental t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 29 publications
0
42
1
4
Order By: Relevance
“…Our study and other previous studies have shown that endotracheal tube size is not associated with PED [1,5]. These results are not consistent with the hypothesis of another study, which stated that endotracheal tube size could affect the severity of PED [24]. However, in our study, the results of endotracheal tube size could not be generalized because the endotracheal tubes used in most patients were similar in size.…”
Section: Discussioncontrasting
confidence: 99%
“…Our study and other previous studies have shown that endotracheal tube size is not associated with PED [1,5]. These results are not consistent with the hypothesis of another study, which stated that endotracheal tube size could affect the severity of PED [24]. However, in our study, the results of endotracheal tube size could not be generalized because the endotracheal tubes used in most patients were similar in size.…”
Section: Discussioncontrasting
confidence: 99%
“…In recent years, many reports have been published on dysphagia in the ICU, and the influence of swallowing disorders on patient prognosis has been attracting attention (Macht et al, , ; Rassameehiran et al, ). The development of post‐extubation dysphagia is independently associated with poor patient outcomes, including post‐extubation pneumonia, re‐intubation, in‐hospital mortality, longer hospital stay, re‐admission to the hospital or entry into nursing home facilities (Macht et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Недавно [113]: изменения в диете, перемена положения тела/компенсаторные вмешательства и интервенционное вмешательство с целью улучшения функции глотания (к примеру, приборы, использующие нервно-мышечную стимуляцию).…”
Section: оценка дисфагии у больных в критическом состоянииunclassified